Pelatihan Pembuatan Biobriket Berbahan Dasar Limbah Ampas Kopi Pillar Coffee Roastery Pekanbaru - Ramadhan, Wahyu; Deri Islami; Brilian Dini Ma. Iballa; Sultan Marganic (Yayasan Rahmatan Fidunya Wal Akhirah, 2025)
Coffee grounds as organic waste from the coffee processing industry such as coffee shops, are often not utilized optimally even though they have the potential as alternative fuels. The accumulation of this waste can have a negative impact on the environment, especially in terms of soil and water pollution. Therefore, this study aims to develop biobriquettes based on coffee grounds waste as a renewable energy solution and to increase the capacity of partners in the production and utilization process. This training program was conducted at Pillar Coffee Roastery, Pekanbaru, with a Pre-Experimental Design (One Group Pre-Test Post-Test) approach to evaluate the effectiveness of training on improving partner understanding and skills. The assessment aspects used were: understanding of biobriquettes, raw materials, production processes, practical skills in making, and the benefits of biobriquettes. The evaluation results from the pre-test and post-test showed that there was an increase in partner understanding in the five assessment aspects, respectively: 48%; 48%; 40%; 46%; 38%. The resulting biobriquettes were tested for calorific value, combustibility, and mechanical resistance, which showed quite good results as an alternative fuel. These biobriquettes can be used as an environmentally friendly alternative fuel. These results prove that the hands- on training approach is effective in increasing the technical capacity and understanding of partners related to renewable energy technology. With the increasing knowledge and skills of partners, it is hoped that this innovation can contribute to sustainable circular economy-based waste management and open up opportunities for the development of green energy-based businesses at the community level.